PEMETAAN DAN ABLASI PADA TAKIKARDIA VENTRIKEL AKIBAT PARUT - Wangko, Loretta C.; Jim, Edmond L. (UNIVERSITAS SAM RATULANGI, 2015)
Abstract: Better understanding of the pathophysiology of ventricular tachycardia (VT) and techniques of mapping as well as ablation leads to higher succes and lower complication rates in the management of patients with VT. Mapping for identification the potential areas for ablation depends on the basic mechanisms of VTs. There are several mapping techniques; each has its own benefit and limitation. The usage of several mapping techniques together shows a higher succes rate. Activation mapping and pacing mapping are very useful in focal VT mechanism meanwhile substrate mapping (with or without pacing mapping) and entrainment mapping are used for reentrant VT mechanism. Nowadays, catheter ablation is an important option for VT cases with ineffective ICD and medication or intolerance, albeit, there is still no complete agreement for the best recommended mapping strategy and ablation techniques for scar-related VT, so far.Keywords: ventricular tachycardia, scar, mapping, ablationAbstrak: Adanya kemajuan pesat baik dalam pemahaman mekanisme patofisiologi takikardia ventrikel (TV) maupun tehnik pemetaan dan ablasi memberikan keberhasilan yang lebih tinggi dan komplikasi yang lebih rendah pada penanganan pasien dengan TV. Pemetaan yang mengidentifikasi area berpotensi untuk dilakukan ablasi bergantung pada mekanisme mendasari terjadinya TV. Terdapat beberapa teknik pemetaan yang dapat digunakan dengan keunggulan dan limitasi masing-masing. Penggunaan beberapa teknik pemetaan bersama-sama dapat dilakukan dengan tingkat keberhasilan yang lebih tinggi. Pemetaan aktivasi dan pemetaan langkah sangat bermanfaat pada mekanisme TV fokal sedangkan pemetaan substrat (dengan atau tanpa pemetaan langkah) dan pemetaan entrainment digunakan untuk mekanisme TV reentrant. Ablasi kateter merupakan pilihan utama untuk kasus TV akibat parut dengan penggunaan ICD dan medikasi yang tidak efektif atau intoleransi namun sampai saat ini belum terdapat rekomendasi yang pasti mengenai strategi pemetaan dan teknik ablasi yang terbaik untuk TV akibat parut.Kata kunci: takikardia ventrikel, parut, pemetaan, ablasi